PEMANFAATAN PEMBELAJARAN LEARNING MANAGEMENT SYSTEM (LMS) DI SMK SYAFI’I AKROM PEKALONGAN - Ika Widiastuti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
SMK Syafi'i Akrom Pekalongan is a vocational education institution that provides education with a national curriculum. During the COVID-19 pandemic, Syafi'i Akrom Vocational School played a role in implementing bold learning. However, there are teachers who have difficulty learning online. According to the Deputy Principal for the Curriculum field, he stated that there were teachers who had difficulty using the Learning Management System application for online learning. Based on the facts in the field, community service so that teachers get guidance in implementing the LMS application, namely Edmodo. Community service is carried out by teachers so they can understand the use of the Edmodo LMS. The purpose of the service is that teachers and students can use and utilize Learning Management System (LMS) learning with the Edmodo application at Syafi'i Akrom Pekalongan Vocational School. the method of service, namely by training carried out by teachers of SMK Syafi'i Akrom Pekalongan presenting 25 participants. The results of the study can be said that the guidance of the Syafi'i Akrom Vocational School teacher in using the LMS application helps carry out learning according to classroom learning. The results showed that 50% of teachers could use Edmodo in terms of sharing materials, assignments and student evaluations.